Social engineering in the concept of rational and irrational consumer behavior - Krestyanpol, Lyubov (Frontiers in Nutrition, 2022)
Consumer behavior as a complex of actions and reactions of a public entity in the field of consumption has been considered, assumptions of the economic component of consumer behavior have been formulated, and recommendations for consideration of consumer behavior in the context of social relations have been given. The formation of consumer behavior from the point of view of psychology has been described. The author has developed and proposed to use a strategy for correcting consumer behavior within the concept of smart packaging. The developed strategies will encourage the consumer to participate in the information system of data collection. The author has considered the levers of influence in rational and irrational behavior, as well as using the methods of social engineering to determine the phases of influence on the consumer.